Estudo da infiltração marginal em restaurações de resinas compostas para dentes posteriores. Efeito do material, preparo cavitário e condicionamento do esmalte a nível cervical. - Marotta Araujo, R.; da Silva Filho, F. P.; Dias Mendes, A. J. (My University, 1990)
The purpose of this in vitro study was to investigate the cervical marginal leakage in class II restorations with chemically cured resin (P10) and light-cured resin (P30) in two types of cavities: conventional and adhesive. The effect of acid-etching in this area was also observed. Dentine adhesive Scotchbond was used in all experimental groups. Leakage was evidenced by Rodamina B dye penetration after thermocycling procedure between 10 degrees C and 50 degrees C temperature and analysed by using Zeiss Stereoscopic Magnifying Glass (10 X). According to the results obtained marginal leakage occurred in all experimental groups, with lower percentage for adhesives cavities when enamel acid-etching and light-cured resin P30 was used.
Marginal leakage in composite resin restorations in posterior teeth. Effect of material, cavity preparation and enamel conditioning at the cervical level
Keywords: P 30 composite resin; P-30 composite resin; resin; scotchbond; tooth cement; cementation; comparative study; dental surgery; human; premolar tooth; review; tooth disease; Acid Etching, Dental; Bicuspid; Comparative Study; Composite Resins; Dental Cavity Preparation; Dental Cements; Dental Leakage; English Abstract; Human